2001
DOI: 10.1074/jbc.m104879200
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Role for Kidney Apolipoprotein E

Abstract: Mesangial expansion is a key feature in the pathogenesis of numerous renal diseases involving the glomerulus. Studies indicate that mutations in apolipoprotein E (apoE) might independently contribute to kidney dysfunction. Although the role of apoE as an atheroprotective molecule is well established, its role in kidney is unclear. In this study, we sought to explore whether apoE has a protective function in kidney. Northern blotting and reverse transcriptase-polymerase chain reaction showed apoE expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 43 publications
(36 reference statements)
2
26
1
1
Order By: Relevance
“…A recent study showed that apo E acts as autocrine regulator of mesangial and glomerular function [17]. Although the mechanism is unclear, our study, that used primary cultured normal human mesangial cells in FCS-free medium, a condition different from theirs, does provide further evidence in the fact that apo E, without causing NHMC apoptosis and interfering cell cycles, increased or decreased NHMC proliferation, and at different days in culture.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…A recent study showed that apo E acts as autocrine regulator of mesangial and glomerular function [17]. Although the mechanism is unclear, our study, that used primary cultured normal human mesangial cells in FCS-free medium, a condition different from theirs, does provide further evidence in the fact that apo E, without causing NHMC apoptosis and interfering cell cycles, increased or decreased NHMC proliferation, and at different days in culture.…”
Section: Discussionsupporting
confidence: 52%
“…The deposition of apo B and apo E in glomeruli accelerates the progression of mesangial lesions [9]. However, this result agreed with Chen’s recent observations in apo E null mice in which there was significant mesangial cell proliferation in glomeruli [17], implying that in normal wild mice apo E directly or indirectly inhibits mesangial cell proliferation. This inhibition was not caused by apoptosis or toxic effect of apo E. Our studies showed that apo E caused no apoptosis, nor did it affect cell cycles.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…For example, disordered apoE function/expression has a well established role in the pathophysiology of important human diseases such as atherosclerosis and dementia (1)(2)(3)(4)(5)(6). ApoE has also been implicated in regulating the expansion of the renal mesangial matrix, in regulating the differentiated function of steroidogenic tissues, and protecting cells from oxidant stress (7)(8)(9). In line with its diverse roles in normal mammalian physiology, apoE is expressed in multiple cell types, including vessel wall macrophages and cells of the central nervous system, in steroidogenic tissue, and in the kidney (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…ApoE has also been implicated in regulating the expansion of the renal mesangial matrix, in regulating the differentiated function of steroidogenic tissues, and protecting cells from oxidant stress (7)(8)(9). In line with its diverse roles in normal mammalian physiology, apoE is expressed in multiple cell types, including vessel wall macrophages and cells of the central nervous system, in steroidogenic tissue, and in the kidney (1)(2)(3)(4)(5)(6)(7)(8)(9). As a surface component of lipoproteins, apoE is involved in regulating organismal lipoprotein metabolism (1)(2)(3)(4).…”
mentioning
confidence: 99%